2020
DOI: 10.3390/math8040469
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Property of Concircular Vector Fields on a Riemannian Manifold

Abstract: In this paper, we show that given a nontrivial concircular vector field u on a Riemannian manifold (M, g) with potential function f , there exists a unique smooth function ρ on M that connects u to the gradient of potential function ∇f , which we call the connecting function of the concircular vector field u. Then this connecting function is shown to be a main ingredient in obtaining characterizations of n-sphere S n (c) and the Euclidean space E n . We also show that the connecting function influences topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Such complete space classifications are extremely attractive and have been studied by several mathematicians (see, e.g., [3,4,6,7,15,16,[18][19][20]). For example, by using (1), Al, Dayel, Deshmukh, and Belova [1] showed that a connected and complete Riemannian manifold ( n , g) is isometric to R n if and only if the nontrivial concircular vector field u along the function ψ satisfies R(∇ψ, ∇ψ) = 0 or u = 0. In [13], Chen and Deshmukh proved that a complete Riemannian manifold admits a concurrent vector field if and only if it is isometric to a Euclidean space by (1).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such complete space classifications are extremely attractive and have been studied by several mathematicians (see, e.g., [3,4,6,7,15,16,[18][19][20]). For example, by using (1), Al, Dayel, Deshmukh, and Belova [1] showed that a connected and complete Riemannian manifold ( n , g) is isometric to R n if and only if the nontrivial concircular vector field u along the function ψ satisfies R(∇ψ, ∇ψ) = 0 or u = 0. In [13], Chen and Deshmukh proved that a complete Riemannian manifold admits a concurrent vector field if and only if it is isometric to a Euclidean space by (1).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For example, by using (1), Al, Dayel, Deshmukh, and Belova [1] showed that a connected and complete Riemannian manifold ( n , g) is isometric to R n if and only if the nontrivial concircular vector field u along the function ψ satisfies R(∇ψ, ∇ψ) = 0 or u = 0. In [13], Chen and Deshmukh proved that a complete Riemannian manifold admits a concurrent vector field if and only if it is isometric to a Euclidean space by (1). Similarly, in [14], it has been shown that ( n , g) is isometric to a Euclidean space if and only if ( n , g) permits a nontrivial gradient conformal vector field, that is, a Jacobi-type vector field.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…e categorization of differential equations on Riemannian manifold has become a fascinating topic of research and has been investigated by numerous researchers, for instance, [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Al-Dayel et al [6] studied the impact of differential equation (2) on Riemannian manifold (L n , g) by taking the concircular vector field and proved that, under certain conditions, the Riemannian manifold (L n , g) is isometric to Euclidean manifold R n . Similarly, by taking gradient conformal vector field, Chen et al [10] identified that Riemannian manifold (N n , g) is isometric to the Euclidean space R n .…”
Section: Introductionmentioning
confidence: 99%
“…The categorization of differential equations on Riemannian manifolds turns into an attractive research subject that has been explored by various researchers, for example, [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%